Medical Image Computing and Computer Assisted Intervention - MICCAI 2022 25th International Conference, Singapore, September 18-22, 2022, Proceedings, Part III - Wang, Linwei; Dou, Qi.; Fletcher, P. Thomas; Speidel, Stefanie; Li, Shuo. (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
The eight-volume set LNCS 13431, 13432, 13433, 13434, 13435, 13436, 13437, and 13438 constitutes the refereed proceedings of the 25th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2022, which was held in Singapore in September 2022. The 574 revised full papers presented were carefully reviewed and selected from 1831 submissions in a double-blind review process. The papers are organized in the following topical sections: Part I: Brain development and atlases; DWI and tractography; functional brain networks; neuroimaging; heart and lung imaging; dermatology; Part II: Computational (integrative) pathology; computational anatomy and physiology; ophthalmology; fetal imaging; Part III: Breast imaging; colonoscopy; computer aided diagnosis; Part IV: Microscopic image analysis; positron emission tomography; ultrasound imaging; video data analysis; image segmentation I; Part V: Image segmentation II; integration of imaging with non-imaging biomarkers; Part VI: Image registration; image reconstruction; Part VII: Image-Guided interventions and surgery; outcome and disease prediction; surgical data science; surgical planning and simulation; machine learning - domain adaptation and generalization; Part VIII: Machine learning - weakly-supervised learning; machine learning - model interpretation; machine learning - uncertainty; machine learning theory and methodologies. .
Breast imaging -- colonoscopy -- computer aided diagnosis.
Keywords: Image processing; Application software; Machine learning; Image processing-Digital techniques; Computer vision; Information technology-Management.; Computers; Image Processing; Computer and Information Systems Applications; Machine Learning; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Application in Administrative Data Processing; Computing Milieux